2015
DOI: 10.5897/ajfs2014.1216
|View full text |Cite
|
Sign up to set email alerts
|

A survey on traditional fish smoking in Lagos State, Nigeria

Abstract: This study examined the socio-economic characteristics, technologies and hygiene of the processors in 20 different 'fish' processing centres in fishing communities in Lagos State. A total of 200 questionnaires were administered through purposive sampling method at 10 respondents/processing centre. Data were collected through field observation and administration of structured questionnaire. Analytical technique used was descriptive statistics. Results reveal that most of the households were relatively poor, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
2
4
2
Order By: Relevance
“…Major results indicated that about 13.3% of the respondents used extended drum oven, 17% galvanized iron sheet, 51% used black clay oven, 31% used red clay, 40% used brick kiln. This result is not in conformity with Adeyeye et al (2005) who cited that majority of fish processors uses full drum in drying their fish. Table 6 revealed sources of energy used by the women in smoking their fish in the study area.…”
Section: Methods Of Processingcontrasting
confidence: 82%
“…Major results indicated that about 13.3% of the respondents used extended drum oven, 17% galvanized iron sheet, 51% used black clay oven, 31% used red clay, 40% used brick kiln. This result is not in conformity with Adeyeye et al (2005) who cited that majority of fish processors uses full drum in drying their fish. Table 6 revealed sources of energy used by the women in smoking their fish in the study area.…”
Section: Methods Of Processingcontrasting
confidence: 82%
“…Concerning performance of the two technologies; chorkor effectively reduced moisture to 10 and 15%, 15 and 17% for M. caschive and O. niloticus smoked using pit, respectively. In line with other studies (Adeyeye et al, 2015;Omodara et al, 2016;Katola and Kapute, 2017;Olukayode and Paulina, 2017), chorkor is an efficient technology for reducing moisture in fish muscle. Effective removal of moisture is attributed to heat concentration linked with the construction materials and enclosed characteristics of chorkor oven.…”
Section: Proximate Chemical Composition Of M Caschive and O Niloticussupporting
confidence: 85%
“…The commonly used smoking technique in Lagos, Nigeria is the 44-gallon drum kiln (Adeyeye et al, 2015) (NIOMR, 2016).…”
Section: Introductionmentioning
confidence: 99%